Web Application for Genetic Modification Flux with Database to Estimate Metabolic Fluxes of Genetic Mutants - Noorlin, Mohd Ali; Tsuboi, Ryo; Matsumoto, Yuta; Koishi, Daisuke; Inoue, Kentaro; Maeda, Kazuhiro; Kurata, Hiroyuki (Elsevier, 2016)
Computational analysis of metabolic fluxes is essential in understanding the structure and function of a metabolic network and in rationally designing genetically modified mutants for an engineering purpose. We had presented the genetic modification flux (GMF) that predicts the flux distribution of a broad range of genetically modified mutants. To enhance the feasibility and usability of GMF, we have developed a web application with a metabolic network database to predict a flux distribution of genetically modified mutants. One hundred and twelve data sets of Escherichia coli, Corynebacterium glutamicum, Saccharomyces cerevisiae, and Chinese hamster ovary were registered as standard models.